La configuración del espacio en la historiografía castellana bajomedieval : una microlectura - Soler, Maximiliano (Estudios de Historia de España, 2016)
The work focuses on the analysis of the representation of space in three episodes in two Chronicles from the middle of the 14th century: the “Leyenda de los jueces de Castilla” (as is preserved in Ms. 431 of Biblioteca Nacional de Madrid), the “Leyenda del pecho de los fijosdalgo” (according to the Primera Crónica General) and the uprising of the nobility in Lerma in 1272 (according to the Crónica de Alfonso X). In each of these episodes the “glera” of Burgos is a privileged scenario in the confrontation of the nobility with the King and contributes also to the configuration of the subjectivity of these social actors under a particular entanglement of historical and legendary subjects. The space acquires, therefore, a new significance which links it socially and politically to this establishment and becomes an emblematic symbol of confrontation.